PENGEMBANGAN MEDIA PEMBELAJARAN KOMIK DIGITAL BERBASIS APLIKASI PIXTON UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN PESERTA DIDIK DI KELAS III SEKOLAH DASAR - Nurkhalifatun Nisa; Indhira Asih Vivi Yandari; Reksa Adya Pribadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to develop a digital comic-based learning medium using thePixton application to improve the understanding of multiplication as repeatedaddition among third-grade elementary school students. The research methodused is the ADDIE development model, which includes Analysis, Design,Development, Implementation, and Evaluation. The Pixton-based digital comicwas validated by a team of experts and teachers before being implemented withthe research subjects, namely third-grade students of SDN Kaloran. The validationtest of the Pixton-based digital comic product received an average scorepercentage of 82% from the expert team, categorized as "very feasible."Meanwhile, the average score percentage from the teachers was 88%, alsocategorized as "very feasible." Based on the validation scores from the expertsand teachers, the average feasibility rating of the Pixton-based digital comic onmultiplication material was 85%, falling into the "very feasible" category. Studentresponses to the Pixton-based digital comic showed an average score percentageof 90.75%, categorized as "very good."The result of the n-gain calculation yieldedan average score of 0.7953, which falls into the "high" category, indicating that theuse of Pixton-based digital comics is effective in improving studentsunderstanding of multiplication. Based on these research results, it can beconcluded that the Pixton application-based digital comic learning medium formultiplication material developed for third-grade elementary students is "veryfeasible" to use in learning and shows that the use of this digital comic is effectivein improving students understanding of multiplication, with a "high" category ofimprovement.